Biofouling in membrane desalination process - Lee, Ricia Jia Rong (2016)
Increasing number of countries are facing water scarcity issues. Membrane desalination processes have become the key technology to provide clean water. However, the main challenge of membrane technology is membrane fouling, which deteriorates the performance of membrane and thus increases the water production cost. Among the fouling types, biofouling is the most common in seawater reverse osmosis (RO) desalination. This study aims to identify the impact of salinity on the biofouling potential of water by characterising the physiological changes and production of extracellular polymeric substances (EPS) of salt-stressed bacteria. The salinity levels tested were 0.6M, 1.2M and 2.4M NaCl, which were equivalent to seawater, 50% and 75% water recovery. Results from the experiments showed that salinity significantly decreased the bacterial growth rate but the cell viability as the live cell/total cell number remained unchanged at around 0.7 to 0.8 for all salinity levels. This may suggest that the bacteria tend to change into viable but non-culturable (VBNC) state under high salinity. On the other hand, the EPS production, i.e. total EPS/total cell count, increased with increasing salinity level. The salt-stressed bacteria produced more EPS to overcome the increase in osmotic pressure. In addition, it was found that the increase in EPS was mainly contributed by the increase in protein concentrations more than the carbohydrate concentrations, which was relatively constant. The results from this study show that the salinity-stressed bacteria still maintain the cell viability and produce more EPS, hence the biofouling potential of water increases with increasing salinity.